2001
DOI: 10.1291/hypres.24.601
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Cardiac Diastolic Function in Hypertensive Patients with Different Left Ventricular Geometric Patterns.

Abstract: To evaluate the alteration of cardiac function in hypertensive patients with different left ventricular geometric patterns. Echocardiography was used to study left ventricular geometry and cardiac diastolic function in 117 cases of essential hypertension, with 45 normal cases as controls. Echocardiographic date were used to calculated the left ventricular mass index (LVMI) and relative wall thickness (RWT), which values in turn were used to divide the subjects into four groups. The left atrial dimension of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
1
3
1
Order By: Relevance
“…Previous studies on hypertensive patients have also reported an association between arterial stiffness and LV structural changes,18) including concentric remodelling and hypertrophy,19) which are themselves associated with diastolic dysfunction 20)21). However, in this study, even in subjects with hypertension with normal LV mass, carotid stiffness was increased with diastolic dysfunction.…”
Section: Discussioncontrasting
confidence: 68%
“…Previous studies on hypertensive patients have also reported an association between arterial stiffness and LV structural changes,18) including concentric remodelling and hypertrophy,19) which are themselves associated with diastolic dysfunction 20)21). However, in this study, even in subjects with hypertension with normal LV mass, carotid stiffness was increased with diastolic dysfunction.…”
Section: Discussioncontrasting
confidence: 68%
“…The echocardiographic determination of atrial and LV dimensions in hypertensive patients clearly indicated that this group of patients had concentric LV hypertrophy, as the patients reported by Qu and collaborators [ 39 ], and that it was associated with the highest degree of diastolic dysfunction.…”
Section: Discussionsupporting
confidence: 53%
“…Other studies have also demonstrated that hypertensive patients may have diastolic dysfunction, regardless of the differences in their structural geometries. 12 , 25 , 38 – 40 In addition, the degree of impairment of cardiac diastolic function differed between hypertensive patients with different LV geometric patterns, 12 , 39 , 40 which was worst in those with concentric geometry. 12 Diastolic dysfunction was observed in incipient stages of hypertensive heart disease, and thus its early detection may help in the risk stratification of hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%